Fundamentals of exercise physiology : for fitness, performance, and health - Robergs, Robert. A.; Keteyian, Steven. J. (Boston : McGraw hill, 2003)
The Ready Notes workbook complements the PowerPoint presentation that accompanies this text. The PowerPoint slides used in class are reproduced in the pages of this booklet. (Instructors can download the PowerPoint presentation at www.mhhe.com/hhp or find it loaded on the Image Presentation CD-ROM that accompanies this textbook.) Lines printed next to each slide allow students to take notes on the PowerPoint presentation as the instructor lectures. Students can later use the PowerPoint images and their own notes to prepare for exams.
Keywords: Exercise -- Physiological aspects; Physical Exertion -- physiology